Pengaruh Pajak Daerah, Retribusi Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Belanja Daerah dengan Pertumbuhan Ekonomi sebagai Variabel Moderating (Studi pada Pemerintah Kabupaten/Kota di Provinsi Jawa Timur) - Jefarina Tavares; Dyah Ani Pangastuti; Edi Subiyantoro (Journal of Regional Economics Indonesia, 2023)
This study aims to analyze the effect of local taxes, regional levies, General Allocation Funds, and Special Allocation Funds on regional spending with economic growth as a moderating variable in district/city governments in East Java province. The data used is secondary data in the form of reports on the realization of the Regional Revenue and Expenditure Budget (APBD) and Gross Regional Domestic Product (GRDP) for 2018-2020. This study used a sample of 114. Data analysis used multiple linear regression analysis and moderated regression analysis (MRA). The results of the study show that local taxes, regional levies, Special Allocation Funds have an effect on regional expenditures, while General Allocation Funds have no effect on regional expenditures. The results of this study also show that economic growth is able to moderate the relationship between regional taxes, regional levies, General Allocation Funds and Special Allocation Funds with regional spending.